Protection of curcumin against amyloid-β-induced cell damage and death involves the prevention from NMDA receptor-mediated intracellular Ca2+ elevation. (3rd September 2015) - Huang, Han-Chang; Chang, Ping; Lu, Shu-Yan; Zheng, Bo-Wen; Jiang, Zhao-Feng
Abstract: Alzheimer's disease (AD) is one of the common neurodegenerative diseases and amyloid-β (Aβ) is thought to be a key molecule contributing to AD pathology. Recently, curcumin is supposed to be beneficial to AD treatment. This study investigates the inhibitory effects of curcumin on Aβ-induced cell damage and death involving NMDA receptor-mediated intracellular Ca 2+ elevation in human neuroblastoma SH-SY5Y cells. Cells were impaired significantly in Aβ-damaged group compared with the control group, and cell viability was decreased while the released LDH from the cytosol was increased. Curcumin promotes cell growth and decreases cell impairment induced by Aβ. Curcmin attenuates Aβ-induced elevation of the ratio of cellular glutamate/γ-aminobutyric acid (GABA) with a concentration-dependent manner. Curcumin inhibits Aβ-induced increase of cellular Ca 2+ and depresses Aβ-induced phosphorylations of both NMDA receptor and cyclic AMP response element-binding protein (CREB) and activating transcription factor 1 (ATF-1). These results indicated that curcumin inhibits Aβ-induced neuronal damage and cell death involving the prevention from intracellular Ca 2+ elevation mediated by the NMDA receptor.